The Role of Physical Exercise in Inflammatory Bowel Disease. (30th April 2014) - Bilski, Jan; Brzozowski, Bartosz; Mazur-Bialy, Agnieszka; Sliwowski, Zbigniew; Brzozowski, Tomasz
Abstract : We reviewed and analyzed the relationship between physical exercise and inflammatory bowel disease (IBD) which covers a group of chronic, relapsing, and remitting intestinal disorders including Crohn's disease (CD) and ulcerative colitis. The etiology of IBD likely involves a combination of genetic predisposition and environmental risk factors. Physical training has been suggested to be protective against the onset of IBD, but there are inconsistencies in the findings of the published literature. Hypertrophy of the mesenteric white adipose tissue (mWAT) is recognized as a characteristic feature of CD, but its importance for the perpetuation of onset of this intestinal disease is unknown. Adipocytes synthesize proinflammatory and anti-inflammatory cytokines. Hypertrophy of mWAT could play a role as a barrier to the inflammatory process, but recent data suggest that deregulation of adipokine secretion is involved in the pathogenesis of CD. Adipocytokines and macrophage mediators perpetuate the intestinal inflammatory process, leading to mucosal ulcerations along the mesenteric border, a typical feature of CD. Contracting skeletal muscles release biologically active myokines, known to exert the direct anti-inflammatory effects, and inhibit the release of proinflammatory mediators from visceral fat. Further research is required to confirm these observations and establish exercise regimes for IBD patients.